Skipping Breakfast Is Associated with an Atherogenic Lipid Profile in Overweight and Obese Prepubertal Children. (10th October 2020) - Blasetti, A.; Franchini, S.; Castorani, V.; Comegna, L.; Fornari, E.; Daniele, F.; Prezioso, G.; Piona, C.; Federico, V.; Zona, D.; Bresadola, I.; Chiarelli, F.; et al.
Abstract : Background . Skipping breakfast has been associated with a higher risk of obesity and cardiovascular (CV) risk factors. However, it is not known if skipping breakfast is also correlated with CV risk factors independently from obesity. The mechanisms explaining the role of skipping breakfast on promoting fat accumulation as well as CV risk are not known. Hormones, in particular, insulin-like growth factor-1 (IGF-1), may potentially play a role in the metabolic profile of breakfast skippers. Aim . This cross-sectional study aims to test, in a sample of overweight/obese children, the hypotheses that skipping breakfast is associated with a worse metabolic profile and that IGF-1 levels are associated with this unfavorable metabolic profile. Methods and Results . We enrolled 112 overweight/obese prepubertal children (3–12 years). Anthropometric characteristics (height SDS, weight SDS, and body mass index (BMI) z -score) were measured. Blood samples were collected to evaluate glucose and lipid metabolisms and hormone profile (growth hormone (GH), IGF-1, insulin, and cortisol). The triglycerides/high-density lipoprotein (HDL) cholesterol ratio was calculated as a predictor of cardiovascular risk. Children were divided into two groups according to breakfast habits: consumers (≥5 weekly; N  = 76) and skippers (≤4 weekly; N  = 36). Glycaemia, total and low-density lipoprotein (LDL) cholesterol, triglycerides (p < 0.05 ), and triglycerides/HDL cholesterol ratio (p < 0.001 ) were higher, while HDL cholesterol was lower (p < 0.01 ) in skippers as compared to consumers. IGF-1 concentrations were inversely correlated with LDL cholesterol ( r  = −0.279, p = 0.013 ) and directly correlated with HDL cholesterol ( r  = 0.226, p = 0.047 ). IGF-1 correlated positively with HDL cholesterol ( r  = 0.266, p = 0.045 ) in consumers and correlated negatively with LDL cholesterol ( r  = −0.442, p = 0.024 ) in skippers. Breakfast consumption among prepubertal overweight/obese children showed a better lipid profile in comparison with those who skipped breakfast [OR: 0.165 (95% CI: 0.053–0.518), p = 0.001 ]; these latter odds of the increased triglycerides/HDL cholesterol ratio was 6.1-fold higher. Conclusions . Breakfast skippers show a worse lipid profile when compared to breakfast consumers. IGF-1 might play a role as an independent modulator of lipid metabolism.